The theory-based view: Economic actors as theorists - Felin, T; Zenger, T (INFORMS, 2017)
This paper outlines the theory-based view of strategy and markets. We argue that novel or “great” strategies come from theories. Entrepreneurs and managers originate theories and hypotheses about which activities they should engage in, which assets they might buy, and how they will create value. A firm’s strategy, then, represents a set of contrarian beliefs and a theory—a unique, firm-specific point of view—about what problems to solve, and how to organize and govern the overall process of value creation. We outline the cognitive and perceptual, organizational and economic foundations of the theory-based view of strategy. We also discuss the essential attributes needed for a firm-level theory of strategy. Throughout the paper we offer informal examples of our argument, by briefly discussing the strategies of companies like Apple, Uber and Airbnb. The theory-based view of strategy and markets also offers important insights for how firms govern themselves (including ownership, boards and organization design) and how firms interact with capital markets and external evaluators and stakeholders. We conclude with a discussion of the practical and managerial applications of the theory-based view.